DISTRIBUTION OF MODIC CHANGES IN MAGNETIC RESONANCE IMAGING OF LUMBAR SPINE - Samad, Mehreen; Khan, Mahnoor Rehman; Khan, Mahrukh Rehman; Tamkeen, Naila; Shahab, Aymen; Rehana, Kanwal (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the frequency and distribution of endplate modic changes in lumbar spine on Magnetic Resonance Imaging (MRI) of lumbar spine of patients with low back pain. Methodology: This cross sectional study was conducted in department of radiology, Hayatabad Medical Complex, Peshawar from January to June 2020. A total 500 patients of both genders were included. MRI films were evaluated by Radiologist with 5 years’ experience. Endplate modic changes were classified according to definition by Modic et al. Frequency and distribution of modic changes were assessed at L1-L2, L2-L3, L3-L4, L4-L5 and L5-S1 levels. Results: In our study, a total of 386 patients showed endplate modic changes. The mean age of the sample was 41.0+15.16 years. There were 190 (47.4% ) males and 196 (52.6%) females. Type 2 modic changes were found in 192 (49.7%) patients while 161 (41.7%) had type 3 modic changes and 33 (8.5%) had type 1 modic changes. Conclusion: Endplate modic changes occur with greater frequency at L5-S1. Modic type 2 changes are most common. Positive correlation exists between degenerative disk disease and modic changes.